The Urgency of Revising Law Number 4 of 1996 on Security Rights to Accommodate Challenges in Collateral Enforcement in the Digital Economy Era - Tiono, Rudi; Rafianti, Fitri; Dahlan (International Conference Epicentrum of Economic Global Framework, 2026)
The rapid development of the digital economy in Indonesia has created complex legal challenges, particularly regarding the execution of collateral rights under Law Number 4 of 1996 concerning Hak Tanggungan atas Tanah Beserta Benda-benda yang Berkaitan dengan Tanah (Undang-Undang Hak Tanggungan). This study critically examines the urgency of reforming Undang-Undang Hak Tanggungan in the context of digital economic transformation, focusing on two central issues the inadequacy of the existing regulatory framework to accommodate digital collateral practices, and the implementation gaps in executing collateral rights in digital-based lending schemes. Using normative legal research with statute, conceptual, and case approaches, this study analyzes primary legal materials including Undang-Undang Hak Tanggungan, Financial Services Authority (OJK) Regulations, Bank Indonesia Regulations, and relevant court decisions. Secondary materials include peer-reviewed journals, academic books, and policy documents. The findings reveal that Undang-Undang Hak Tanggungan fundamentally lacks provisions for digital collateral documentation, electronic signatures, and fintech-based collateral execution. The absence of clear legal mechanisms for executing collateral rights in peer-to-peer lending and digital banking transactions creates systemic legal uncertainty. This study concludes that comprehensive legislative reform of Undang-Undang Hak Tanggungan is urgently needed, incorporating digital identity verification, electronic deed recognition, and streamlined e-execution procedures, while maintaining creditor-debtor balance and public interest protection.